Inside or out? Possible genomic consequences of extracellular transmission of crypt-dwelling stinkbug mutualists - Otero Bravo, Alejandro; Sabree, Zakee L. (Frontiers in Ecology and Evolution, 2015)
Genome reduction has been widely studied in obligate intracellular bacterial mutualists of insects because they have, in comparison to closely-related, nonhost-associated bacteria, extremely small genomes. Pentatomid stinkbugs also maintain bacterial symbionts, yet they are extracellular, residing within host-derived crypts, and are transmitted to offspring outside of the host's tissues, which exposes them to the external environment. In this review, we explore how the biphasic lifestyle of stinkbug symbionts (e.g. on the surfaces of eggs in various matrices during transmission and inside host-derived tissues during much of the host's life), in contrast with the solely intracellular lifestyle of many insect endosymbionts, may impact their genome's architecture, size and content. Furthermore, we demonstrate how additional stinkbug symbiont genomes are needed to more fully explore these questions and the potential value of the stinkbug-symbiont system in understanding genome evolution and reduction in the absence of intracellularity.